Optically Mediated Hybridization between Two Mechanical Modes - Shkarin, A. B.; Flowers-Jacobs, N. E.; Hoch, S. W.; Kashkanova, A. D.; Deutsch, C.; Reichel, J.; Harris, J. G. E. (Physical review letters, 2014)
In this Letter we study a system consisting of two nearly degenerate mechanical modes that couple to a single mode of an optical cavity. We show that this coupling leads to nearly complete (99.5%) hybridization of the two mechanical modes into a bright mode that experiences strong optomechanical interactions and a dark mode that experiences almost no optomechanical interactions. We use this hybridization to transfer energy between the mechanical modes with 40% efficiency.